Relationships between socio‐clinico‐demographic factors and global cognitive function in the oldest old living in the Tokyo Metropolitan area: Reanalysis of the Tokyo Oldest Old Survey on Total Health (TOOTH). (7th March 2018) - Eguchi, Yoko; Tasato, Kumiko; Nakajima, Shinichiro; Noda, Yoshihiro; Tsugawa, Sakiko; Shinagawa, Shunichiro; Niimura, Hidehito; Hirose, Nobuyoshi; Arai, Yasumichi; Mimura, Masaru
Abstract : Background: Despite a steady increase in life expectancy, a few studies have investigated cross‐sectional correlates and longitudinal predictors of cognitive function, a core domain of the successful aging, among socio‐clinico‐demographic factors in the oldest‐old exclusively. Objectives: The aims of this study were to examine socio‐clinico‐demographic characteristics associated with global cognition and its changes in the oldest‐old. Methods: We reanalyzed a dataset of cognitively preserved community‐dwelling subjects aged 85 years and older in the Tokyo Oldest Old Survey on Total Health, a 6‐year longitudinal observational study. This study consisted of (1) baseline cross‐sectional analyses examining correlates of global cognition (n = 248) among socio‐clinico‐demographic factors and (2) longitudinal analyses examining baseline predictors for changes of global cognition in 3‐year follow‐up (n = 195). The Mini‐Mental State Examination was used as a screening test to assess global cognition. Results: At baseline, higher weights were related to higher cognitive function in the oldest‐old. The baseline predictors of global cognitive decline in 3‐year follow‐up were higher global cognition, shorter education period, and lower sociocultural activities and lower instrumental activity of daily living, in this order. Conclusions: The present study suggests that it is crucial to attain higher education during early life and avoid leanness or obesity, participate in sociocultural cognitive activities during late life, and maintain instrumental activity of daily living to preserve optimal cognitive function in the oldest‐old, which will facilitate developing prevention strategies for cognitive decline and promoting successful aging in this increasing population.